Employee Management System for Enterprise Company (International Journal of Innovative Computing, 2024)
During this revolutionizing global market, enterprise companies of today must respond dynamically to changes in order to survive the future. The changes compel all business owners to adjust themselves and adapt to new strategies in managing their businesses. Previously, employee management was done manually by most of the company or organization and it requires a huge effort in internal management to ensure an optimum level of their business productivity. In recent years, there has been a significant advancement in technology that allows the company to transform the manual process of employee management into a digitized process through the development of software or web application. Employee management has been undergoing considerable change over the past few decades, as most industries have realized the potential of technology to improve employee management and information. Therefore, an Employee Management System is proposed to solve the problems. The methodology used to develop this system is Agile methodology. Agile methodology focuses on the iteration cycle that splits the development process into different phases which are known as sprints. The phases of Agile methodology consists of requirements, analysis, design, implementation and testing. The system requirements are gathered by using the elicitation techniques such as interview, survey, literature reviews and prototyping. These requirements are represented using Unified Modeling Language (UML) including use case diagram, sequence diagram and activity diagram and then documented into Software Requirement Specification (SRS). A complete and overall design of the system which includes system architecture design, database design, interface design and test case design are conducted and documented into Software Design Document (SDD) and Software Testing Documentation (STD). At the end of this project, an intuitive Employee Management System is developed and could be fully functional to improve the effectiveness of the employee management in the company.
Keywords: Employee management, employee management system, management system, employee